An Analysis of Deixis in Fast X Movie (2025) - Gustiana, Resti; Adawiyah, Siti Saadatul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of the study explores the phenomenon of deixis defined in linguistic terms as expressions whose interpretation is relative to the context of the utterance (e.g., speaker, time, and place) in the movie Fast X. The objective is to categorize and analyze the usage of deictic expressions based on Levinson’s (1983) classification: personal deixis (e.g., I, you), spatial deixis (e.g., here, there), temporal deixis (e.g., now, then), discourse deixis (e.g., this, that referring to parts of the text), and social deixis (e.g., sir, madam indicating social status). Using a descriptive qualitative method, the researcher collected data by transcribing character dialogues from the film. Language data were analyzed in terms of deixis reference, contextual dependency, and pragmatic function. The study finds that personal deixis is the most dominant type, reflecting the interpersonal dynamics and narrative perspective. This study highlights the importance of deixis in cinematic language, significance of deixis in enhancing coherence and engagement in film storytelling. Keywords: deixis, levinson’s theory, pragmatics, linguistics.